Symptoms Induction by Pseudorecombination of RNA Species Between CMV Strains - W. S. Wahyuni; Y. Sulyo; I. B. Raharjo; E. B. Trisusilowati (Jurnal Perlindungan Tanaman Indonesia, 2000)
Twenty seven strains of CMV have been collected throughout Java, they have four RNA species and none of them contain satellite RNA. The exchange of RNA species of strains belonging to subgroup I and II for pseudorecombination induced mild to severe symptoms on Nicotiana glutinosa. By aphid transmission, the CMV pseudorecombinant could produce a typical symptom of one of its parental strain or expressed unlikely symptoms as those of either parental strains on N. glutinosa. Some plants with mild symptoms were detected to be positive by Indirect ELISA.